2016
DOI: 10.1161/jaha.116.003521
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Mtus1 Splice Variant as a Novel Inhibitory Factor Against Cardiac Hypertrophy

Abstract: BackgroundIn cardiac hypertrophy and failure, there is a widespread alteration in mRNA splicing, but the role of splice variants in cardiac hypertrophy has not yet been fully elucidated. In this study, we used an exon array to identify novel splice variants associated with cardiac hypertrophy.Methods and ResultsWe performed genome‐wide exon array analysis and developed a splicing profile in murine hearts with hypertrophy induced by transverse aortic constriction for 8 weeks. Following global analysis of splice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Meanwhile, other studies found that MTUS1 was associated with the microtubule cytoskeleton and localized at the centrosome and mitotic spindle in dividing breast cancer cells (27). It was recently reported that a splice variant of mouse MTUS1a, which is highly homologous to human transcript variant 5, was localized in the mitochondria, whereas MTUS1c, which is highly homologous to human transcript variants 1 and 2 of MTUS1, was colocalized with a-tubulin in cardiomyocytes (15). One possible reason of the distinct cellular localization of MTUS1 is that multiple alternatively spliced transcript variants, which encode different isoforms of MTUS1, are expressed in a cell type-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, other studies found that MTUS1 was associated with the microtubule cytoskeleton and localized at the centrosome and mitotic spindle in dividing breast cancer cells (27). It was recently reported that a splice variant of mouse MTUS1a, which is highly homologous to human transcript variant 5, was localized in the mitochondria, whereas MTUS1c, which is highly homologous to human transcript variants 1 and 2 of MTUS1, was colocalized with a-tubulin in cardiomyocytes (15). One possible reason of the distinct cellular localization of MTUS1 is that multiple alternatively spliced transcript variants, which encode different isoforms of MTUS1, are expressed in a cell type-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…MTUS1 deficiency is implicated in multiple types of cancers. It reportedly plays important roles in vascular remodeling (12), adipocyte differentiation (13), lymphocytosis, and cardiac hypertrophy (14,15). We recently reported that MTUS1 transcript variant 5 is the most abundant isoform in ECs, and the loss of MTUS1 resulted in cAMP response element-binding protein (CREB) binding protein (CREBBP)-mediated NF-kB activation in ECs (16).…”
mentioning
confidence: 99%
“…Interestingly, ATIP1 has also been identified as mitochondrial tumor suppressor gene 1 (MTSG1 coded by Mtus1A) whose overexpression suppresses mitochondrial ROS production, ERK activation, and hypertrophy in response to phenylephrine in cardiac myocytes. However, the functional relation of the phenotype with AT 2 R remains unclear (424).…”
Section: B Angiotensin Type 2 Receptormentioning
confidence: 99%
“…A previous study reported that CALR (calreticulin) [124], BSCL2 [125], PKD1 [126], TMBIM1 [127], CHST15 [128] [190], SLC2A4 [191], HLA-DOA [192], TAP2 [193], HLA-DPA1 [194], NSMCE2 [195], NDUFA4 [196], HMG20A [197], AMY2B [198] and ACYP2 [199] might be involved in the pathogenesis of diabetics, but these genes might be novel target for HF. Recent evidence indicates that the SIRPA (signal regulatory protein alpha) [200], PFN1 [201], EIF6 [202], AHR (aryl hydrocarbon receptor) [203], RUNX1 [204], IDO1 [205], PDHB (pyruvate dehydrogenase E1 subunit beta) [206], NDUFS1 [207], MTUS1 [208], ZNF418 [209] and MTMR14 [210] are the key biomarkers in cardiac hypertrophy. Previous studies had shown that the expression of CLIC1 [211], ARPC1B [212], FLNA (filamin A) [213], HILPDA (hypoxia inducible lipid droplet associated) [214], RTN3 [215], G0S2 [216], CALU (calumenin) [217], MYDGF (myeloid derived growth factor) [218], LTBR (lymphotoxin beta receptor) [219], GGCX (gamma-glutamyl carboxylase) [220], SAMD1 [221], ACAT1 [222], NNT (nicotinamide nucleotide transhydrogenase) [223] and ATG14 [224] were closely related to the occurrence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%